2022
DOI: 10.1039/d2qi00968d
|View full text |Cite
|
Sign up to set email alerts
|

Study on the thermal decomposition behavior of ammonium perchlorate catalyzed by Zn–Co cooperation in MOF

Abstract: The combustion performance of solid propellant plays a decisive role in the overall application of the rocket. Changing decompose behavior of ammonium perchlorate (AP) by adding catalyst is an effective...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…In contrast, the mass loss trend of PB-NSa-N 2 proves that its decomposition behavior has not stopped at 500 °C and further testify that in the presence of AP actual catalytic component is the final product Fe 2 O 3 , which is consistent with our previous research. [48,49] In addition, the TG test after mixing PB-NSa and AP with 1:1 mass ratio further confirms the above conclusion (Figure 4b). The rapid loss and gradual flattening of total mass near 300 °C indicated the rapid decomposition of AP and PB-NSa in this process.…”
Section: Discussion On Catalytic Mechanismsupporting
confidence: 78%
See 1 more Smart Citation
“…In contrast, the mass loss trend of PB-NSa-N 2 proves that its decomposition behavior has not stopped at 500 °C and further testify that in the presence of AP actual catalytic component is the final product Fe 2 O 3 , which is consistent with our previous research. [48,49] In addition, the TG test after mixing PB-NSa and AP with 1:1 mass ratio further confirms the above conclusion (Figure 4b). The rapid loss and gradual flattening of total mass near 300 °C indicated the rapid decomposition of AP and PB-NSa in this process.…”
Section: Discussion On Catalytic Mechanismsupporting
confidence: 78%
“…The results showed that the high‐temperature decomposition peak of AP was reduced to 322.1 °C, and the heat release was increased to 1922 J g −1 . [ 25 ] However, although the improvement of agglomeration of active components in the catalytic process has been considered (using metal organic framework(MOF)‐based catalyst), it cannot be solved, which is reflected in the change of activation energy at different reaction levels. Therefore, it is of great significance to explore the appropriate structure of the catalyst and the interaction form between the catalyst and AP for achieving high catalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…5 Ammonium perchlorate (AP), the most commonly used oxidizer, comprises around 60-90% of the total content of CSPs and is known for its high oxygen level, high thermal stability, large combustion gas production per unit content, and great oxidation performance. 4,6 Owing to the aforementioned properties, AP is regarded as an irreplaceable oxidizer. Being the major component, the thermal behaviour of AP directly inuences the propellant performance and is highly sensitive to the presence of additives.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, due to the anchoring effect, carbon nanomaterials can also promote the uniform diffusion of ECs to the surrounding region, forming a more uniform composite material with a larger contact area, which improves the transport capacity of electrons to a certain extent, thus enhancing the ability to promote the thermal decomposition of AP. 30,31…”
Section: Introductionmentioning
confidence: 99%